(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The article focuses on the latest developments of the CoViD-19 emergency and, specifically, on the issue of an emergency legislation that does not completely comply with the constitutional safeguards. Therefore, the aim of this analysis is to suggest a different solution respectful of the constitutional framework. In order to prevent a misleading interpretation of the new emergency regulations, the author suggests an analogical and evolutionary interpretation of art. 78 Const. Otherwise, the future will be characterized by legal uncertainty.